FAKTOR–FAKTOR KEBERHASILAN WIRAUSAHA MAHASISWA BERBASIS MARKETING MIX 7P - Susantiningrum Susantiningrum; Edy Legowo; LV Ratna Devi Sakuntalawati; Irsyadul Ibad; Dyah Yuni Kurniawati; Nur Rahmi Akbarini (Universitas Sebelas Maret, 2021)
The level of success of PMW in several universities in producing new entrepreneurs (WUB) is still not optimal. Failure factors dominate PMW students more than success factors. Therefore, the purpose of this study is to analyze the success factors of student entrepreneurship based on the 7P Marketing Mix. The research method used is quantitative research. The results showed that in culinary and non-culinary businesses, the same success factors are in the elements of price, promotion, place, people, and process. In culinary, non-culinary, and service businesses, the same success factor lies in the process element. The similarities that do not exist in all elements indicate that the success factors found in the three business groups have their own uniquenessKeywords: Marketing Mix 7P, Student Entrepreneurship, Success Factors